(3QSGdI aj GdCSFdI GdWHjYI GdMGQKjIs - (3GdMGQK Hf cdOI , GdMGQK Hf cdOI GdKbaj,J (B50 (3g` s
(3ChdgG (B:s
(3haO GdMGQK Hf cdOI Ydi cSQi CHh TQhGf GdYGOd adeG eKd Hjf jOjg bGd dg cSQi cja HUQc HGdWH bGd eG Ud GdWH bGd VHW GdTaJjf hGdOab HGdjOjf s
(3BNQgG (B:s
(3bGd YfO RjdGf GdTeS fQjOc GdfXQ Zdi UHGMI hLggG hKeQGJ HOfgG GfJTGQkG hdPI bGd cSQi ddg OQc ef EYQGHi CYWjH YdekG hhUdg hbGe Edi fSGFg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B176s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs